Exploring the bidirectional causal link between household income status and genetic susceptibility to neurological diseases: findings from a Mendelian randomization study - Weidong Nong; Gui Mo; Chun Luo (Frontiers in Public Health, 2023)
ObjectivesObservational studies have revealed that socioeconomic status is associated with neurological disorders and aging. However, the potential causal effect between the two remains unclear. We therefore aimed to investigate the causal relationship between household income status and genetic susceptibility to neurological diseases using a bidirectional Mendelian randomization (MR) study.MethodsAn MR study was conducted on a large-sample cohort of the European population pulled from a publicly available genome-wide association study dataset, using a random-effects inverse-variance weighting model as the main standard. MR-Egger regression, weighted median, and maximum likelihood estimation were also performed concurrently as supplements. A sensitivity analysis, consisting of a heterogeneity test and horizontal pleiotropy test, was performed using Cochran’s Q, MR-Egger intercept, and MR-PRESSO tests to ensure the reliability of the conclusion.ResultsThe results suggested that higher household income tended to lower the risk of genetic susceptibility to Alzheimer’s disease (odds ratio [OR]: 0.740, 95% confidence interval [CI] = 0.559–0.980, p-value = 0.036) and ischemic stroke (OR: 0.801, 95% CI = 0.662–0.968, p-value = 0.022). By contrast, higher household income tended to increase the risk of genetic susceptibility to Parkinson’s disease (OR: 2.605, 95% CI = 1.413–4.802, p-value = 0.002). No associations were evident for intracranial hemorrhage (OR: 1.002, 95% CI = 0.607–1.653, p-value = 0.993), cerebral aneurysm (OR: 0.597, 95% CI = 0.243–1.465, p-value = 0.260), subarachnoid hemorrhage (OR: 1.474, 95% CI = 0.699–3.110, p-value = 0.308), or epilepsy (OR: 1.029, 95% CI = 0.662–1.600, p-value = 0.899). The reverse MR study suggested no reverse causal relationship between neurological disorders and household income status. A sensitivity analysis verified the reliability of the results.ConclusionOur results revealed that the populations with a superior household income exhibit an increased predisposition of genetic susceptibility to Parkinson’s Disease, while demonstrating a potential decreased genetic susceptibility to ischemic stroke and Alzheimer’s disease.